MicroRNAs: tiny molecules with a significant role in mammalian follicular and oocyte development. Issue 3 (March 2018) - Tesfaye, Dawit; Gebremedhn, Samuel; Salilew-Wondim, Dessie; Hailay, Tsige; Hoelker, Michael; Grosse-Brinkhaus, Christine; Schellander, Karl
Abstract : The genetic regulation of female fertility (follicular development, oocyte maturation and early preimplantation embryo development) involves the spatio-temporal regulation of those genes that play key roles in various stages of the female reproductive axis. MicroRNAs (miRNAs), a class of small non-coding RNAs, are known to regulate the expression of a large proportion of such genes. In recent decades, multiple studies have aimed to determine the roles of these non-coding RNAs in mammalian follicular development, oocyte growth and embryo development. These studies have applied a variety of approaches, including conditional knockout of miRNA biogenesis genes, high-throughput sequencing technologies for pattern recognition in miRNA expression and loss- and gain-of-function of miRNAs in various animal models. In addition to the cellular miRNAs, a large variety of RNAs are found in circulation, being coupled with extracellular vesicles, proteins and lipids. Because of their potential as diagnostic markers for abnormal physiologies, there is increasing interest in the identification of extracellular miRNAs in various biological fluids and spent in vitro culture media. This review focuses on studies addressing the expression and potential role of cellular and extracellular miRNAs in mammalian follicular cell physiology and subsequent ovarian functionality and oocyte maturation.